Budd-Chiari syndrome following vaginal delivery in a patient with Crohn's disease: a case report and review of the literature - Aygun, Banu Kumbak; Pinar, Gulser Goktolga; Sahin, Levent; Ozkan, Zehra Sema; Poyraz, Ahmet Kursad; Aygun, Cem (Walter de Gruyter Gmbh, 2013)
Introduction: The association of Budd-Chiari syndrome (BCS), Crohn ' s disease (CD) and pregnancy is extremely rare. The successful medical treatment of BCS in the postpartum period in a woman with CD is presented. Case report: A 28-year-old woman with CD presented with fever of 42 degrees C and gross abdominal distention 2 days following delivery. On sonographic examination, massive ascites and hepatosplenomegaly were noted. Color Doppler ultrasonography and contrast-enhanced computed tomography revealed a thrombus in the suprahepatic inferior vena cava causing significant luminal obstruction. She was diagnosed with BCS. Medical treatment with spironolactone, furosemide, imipenem, metronidazole, and enoxaparin improved the clinical picture. Conclusion: In a pregnant woman with CD, extreme thromboembolic events such as BCS might occur. If diagnosed early and treated in the acute phase, prognosis is fair.
Keywords: Budd-Chiari syndrome; Crohn's disease; pregnancy; puerperium